(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Chronic smoking is often associated with chronic obstructive pulmonary disease, coronary artery disease, hypertension & aortic aneurysm in elderly people. However its life threatening complications in the form of tension pneumothorax, mediastinal emphysema, and enlarging aortic aneurysm coexisting with pulmonary tuberculosis at times poses diagnostic and therapeutic challenge. We report here with an 86 - year - old male who had mediastinal emphysema, large aortic aneurysm, accelerated hypertension and evidence of active pulmonary tuberculosis aggravated by chronic smoking. He made remarkable recovery following intercostal drainage, anti tuberculous and supportive intensive therapy. Keywords: Chronic obstructive pulmonary disease; Pneumothorax; Mediastinal emphysema; Aortic aneurysm; Hypertension; Pulmonary tuberculosis DOI: 10.3126/saarctb.v5i2.3073 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(2) 26-30